PENGEMBANGAN BAHAN AJAR BERBASIS CERITA BERGAMBAR PADA PEMBELAJARAN TEMATIK KELAS II SEKOLAH DASAR - Ega Indriani; Tahmid Sabri; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to produce teaching materials based on pictorial stories on thematic learning in class II theme 4 sub-theme 2 Clean and Healthy Living in Schools. This type of research is a development research using a model ADDIE with analysis, design, development, implementation, evaluation steps. Data quantitative data comes from the score of the product assessment results by the validator as well as from the results of filling out a questionnaire on the practicality of teaching materials by teachers and students. Qualitative data obtained from suggestions and notes by the validator. The level of validity of teaching materials based on the results of assessments by experts design and material experts while the practicality of teaching materials is based on the results of the assessment by students and teachers of class II Public Elementary School 35 South Pontianak. Results validation of teaching materials design experts obtained an average of 4.1 with the "valid" category. Results expert validation of teaching materials obtained an average of 3.8 in the "valid" category. Results the practicality of teaching materials by students obtained an average of 3.6 with the category "very" practical". The results of the practicality assessment of teaching materials by teachers obtained an average of 3.4 with the “very practical” category.Keywords: Comic, Development, Teaching Materials